Evaluation of the PEN-FAST clinical decision rule in non-beta-lactam antibiotic allergy assessment - Göcebe, Deniz; Khatamzas, Elham; Enk, Alexander; Schäkel, Knut (Annals of allergy, asthma and immunology, 2025)
Background - False antibiotic allergy labels lead to the unnecessary use of broad-spectrum agents, contributing to antimicrobial resistance and poorer clinical outcomes. Penicillin allergy delabeling initiatives have been supported by validated clinical decision rules such as PEN-FAST. However, there are currently no available standardized approaches for non-beta-lactam allergies, for which standardized and validated skin tests are also lacking. - Objective - First, to validate the safety and negative predictive value (NPV) of PEN-FAST for penicillin allergies. Second, to evaluate whether the performance of PEN-FAST could be replicated for non-beta-lactam antibiotic allergy labels. - Methods - This retrospective single-center comparative cohort study analyzed adult patients with penicillin or non-beta-lactam allergy labels referred to our allergy division at the Department of Dermatology, Heidelberg, Germany. Allergy assessment included skin tests and subsequent drug challenge. The performance of the previously published PEN-FAST criteria was evaluated for both cohorts. - Results - A total of 102 penicillin allergy and 191 non-beta-lactam labels were analyzed. Confirmed allergies were more prevalent among non-beta-lactams (50.3% vs 37.3%). PEN-FAST exhibited high sensitivity for both penicillin (97.4%) and non-beta-lactams (94.8%), with an NPV of 95.8% and 82.8%, respectively. Misclassifications were limited to mild cutaneous reactions. Excluding clindamycin labels increased the NPV for non-beta-lactams to 95%. - Conclusion - Despite lower NPV for non-beta-lactam labels and varying performance across antibiotic classes, our results indicate that PEN-FAST may serve as a safe risk stratification tool for non-beta-lactam allergy labels. Prospective studies with direct drug challenges are required to assess its utility in the delabeling of non-beta-lactam allergies.
Online verfügbar: 21. Juni 2025, Artikelversion: 30. September 2025
Gesehen am 26.01.2026